2018
DOI: 10.1001/jamaophthalmol.2018.1501
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Nonmetastatic Unilateral Retinoblastoma in Children

Abstract: IMPORTANCE Multi-institutional collaborative studies that include large patient populations for the management of retinoblastoma with histopathological risk factors could provide important information for patient management. OBJECTIVE To evaluate the implementation of a strategy for the management of nonmetastatic unilateral retinoblastoma in children based on standardized diagnostic and treatment criteria. DESIGN, SETTING, AND PARTICIPANTS This single-arm prospective study applied a strategy based on a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 38 publications
0
42
2
Order By: Relevance
“…Twenty-three (51%) had delayed enucleation, and their OS was 0.60 ± 0.13. Although we could not perform accurate comparisons with the prior study because of the lack of complete documentation of buphthalmos, these results are comparable to the Pérez et al 31 Grupo de America Latina de Oncología Pediátrica cohort with buphthalmos treated with neoadjuvant chemotherapy, where one of seven patients with buphthalmos experienced a relapse.…”
Section: Discussioncontrasting
confidence: 54%
“…Twenty-three (51%) had delayed enucleation, and their OS was 0.60 ± 0.13. Although we could not perform accurate comparisons with the prior study because of the lack of complete documentation of buphthalmos, these results are comparable to the Pérez et al 31 Grupo de America Latina de Oncología Pediátrica cohort with buphthalmos treated with neoadjuvant chemotherapy, where one of seven patients with buphthalmos experienced a relapse.…”
Section: Discussioncontrasting
confidence: 54%
“…Intraocular retinoblastoma requires access to an experienced ophthalmologist for an immediate examination underanesthesia (EUA) to determine the intraocular extent of disease (cT1‐CT3) and laterality, as this will determine treatment with either local therapy or local and systemic chemotherapy. Routine neuroimaging (MRI) for unilateral intraocular retinoblastoma could be deferred unless there is involvement of the optic nerve or a suspicion of extraocular involvement 39 . Given the likely resource constraints for interventional radiology and prolonged anesthesia, services should consider deferring intraarterial chemotherapy programs.…”
Section: Retinoblastomamentioning
confidence: 99%
“…Overall survival was 100% in the low-risk group without receiving systemic chemotherapy and 95% in the high-risk group. The authors suggested that adjuvant chemotherapy may not be necessary for low-risk patients but benefits patients with high-risk retinoblastoma in preventing extraocular relapse [ 10 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…Tumors become advanced if treatment is delayed, hindering vision and globe salvages with a risk of metastasis [ 8 , 9 , 10 ]. Chemotherapy is the standard of care for patients with a high risk of metastasis but has inevitable toxicity [ 10 , 11 , 12 , 13 , 14 , 15 ]. Such treatment is also commonly used for globe sparing with different routes of drug delivery depending on the clinical features and anticipated outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%